2013
DOI: 10.1093/eurheartj/eht293
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of coronary computed tomography angiography during 5 years of follow-up in patients with suspected coronary artery disease

Abstract: Data from CCTA predict both death and myocardial infarction as well as need for subsequent revascularizations out to 5 years. CCTA imaging may be a valuable tool in the assessment of long-term prognosis in patients with suspected CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(64 citation statements)
references
References 20 publications
5
56
3
Order By: Relevance
“…Although older studies have compared the prognostic value of stress testing within each sex, there are few contemporary data on this issue (5-7). Furthermore, recent observational studies on the prognostic value of computed tomographic angiography (CTA) do not include sex-specific analyses (8,9). A fuller understanding of the prognostic performance of these tests could aid in selecting the diagnostic evaluation strategy for both women and men.…”
mentioning
confidence: 99%
“…Although older studies have compared the prognostic value of stress testing within each sex, there are few contemporary data on this issue (5-7). Furthermore, recent observational studies on the prognostic value of computed tomographic angiography (CTA) do not include sex-specific analyses (8,9). A fuller understanding of the prognostic performance of these tests could aid in selecting the diagnostic evaluation strategy for both women and men.…”
mentioning
confidence: 99%
“…Similar to coronary angiography, a stepwise deterioration in prognosis associated with 1-, 2-, and 3-vessel disease has been observed using coronary CTA (49). Coronary CTA has also documented the adverse prognosis associated with nonobstructive disease (not detected with standard perfusion assessments) and confirmed the excellent prognosis for patients with a normal coronary CTA, with a risk of cardiovascular events of <0.5% that extends up to 5 years (50). Coupled with the excellent negative predictive value of a normal scan, coronary CTA is recommended in ruling out coronary artery disease in those considered at low or intermediate risk (51).…”
Section: Coronary Angiographymentioning
confidence: 72%
“…In parallel, several retrospective analyses have demonstrated that CTCA-based imaging provides useful prognostic information and enables detection of patients that are likely to suffer a cardiovascular event amongst individuals with suspected CAD [95][96][97][98]146,147]. In patients with established CAD, a small scale study showed that CTCAderived variables were predictors of MACE at 5-year followup and improved considerably the prognostic accuracy of the model developed from the clinical variables (from 0.68 to 0.76) [148].…”
Section: Expert Commentarymentioning
confidence: 99%